MORAL VALUES IN HAYAO MIYAZAKI’S SPIRITED AWAY: A SOCIOLOGY OF LITERATURE APPROACH - Noviana, Fajria (Faculty of Humanities, Diponegoro University, 2020)
Moral is what guides human to act humanly. That is why moral education should be taught as early as possible in order to make a society that upholds moral values. This paper focused on moral values of the Japanese that can be seen in Miyazaki’s anime entitled Spirited Away. The moral values discussed in this paper are based on Japanese moral education for elementary school level, which divided into four groups of desirable habits. They are matters belonging to oneself, relationship of self to other persons, matters related chiefly to nature and sublime things, and matters concerning the group and society. The determination of this level is due to the behavior of the main character named Chihiro who was an elementary school student, which is used as a guide to discussing moral values consisted in the anime. The conclusion is that the Japanese government has succeeded in giving moral education in elementary school, at least in this anime. Chihiro's actions are proof that she acts and reacts as what she taught in Japanese elementary school. She did exactly the same with recommended traits in the four groups of desirable habits, although she sometimes broke the rules which was natural for human being, especially for kids. Therefore, we can say that well-structured Japanese moral education can be used in much wider place; not only in Japan but also in other countries.